Métodos analíticos nucleares aplicados à compreensão da origem e do transporte de sedimentos recentes - Carvalho, Carla Regina Alves (2009)
This work aims to study the provenance and transport processes of sediment along the Southern Coast of Rio de Janeiro State, using the natural gamma radiation technique, through measurements of thorium, uranium and potassium concentrations. Such measurements enabled a statistical study of eTh/eU and eTh/K cross plots, which reflect the mineralogical properties of sediments, as well as its history of transport and sedimentation. The area of interest is located within the Ilha Grande bay, in the so-called Costa Verde or the Brazilian Green Coast, covering the coastal strip from Brava (23o00 S e 44o28 W) to São Gonçalo beaches (23o02 S e 44o37 W). The results show the different origins of the coastal sediments studied and showed the influence of the Rio Mambucaba to this mixture. Moreover, the distribution of heavy minerals along this area could be mapped and described by a geographical model, reflecting the importance of fluvial transport of sediments to the coast, where they are deposited. On the other hand, it was possible to verify the importance of waves and currents to the region geomorphology as well, since higher concentrations of heavy minerals were only observed at specific locations. Finally, the results have shown that the NaI detector can be rather efficient for this kind of study. In what concerns laboratory measurements, provided concentrations are not extremely low, it is possible to use such kind of detector, more economically viable than a higher resolution detector as the HPGe and easier to maintain. This technique proved to be an important auxiliary tool to standard geophysical methods and, in some cases, being able to substitute these needing less financial resources.